2022
DOI: 10.1609/aaai.v36i1.19933
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Attention Gated Network for Pedestrian Trajectory Prediction

Abstract: Pedestrian trajectory prediction is crucial in many practical applications due to the diversity of pedestrian movements, such as social interactions and individual motion behaviors. With similar observable trajectories and social environments, different pedestrians may make completely different future decisions. However, most existing methods only focus on the frequent modal of the trajectory and thus are difficult to generalize to the peculiar scenario, which leads to the decline of the multimodal fitting abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Different from other methods, SIT embed the future pedestrian trajectories into a discrete structure space, and it has a better performance on long-term prediction work. •CAGN [ 52 ] …”
Section: Methodsmentioning
confidence: 99%
“…Different from other methods, SIT embed the future pedestrian trajectories into a discrete structure space, and it has a better performance on long-term prediction work. •CAGN [ 52 ] …”
Section: Methodsmentioning
confidence: 99%
“…RNN structure has widely been used to capture temporal dependencies while considering social interactions using pooling mechanism (Alahi et al 2016;Bisagno, Zhang, and Conci 2018;Gupta et al 2018) or attention mechanism (Vemula, Muelling, and Oh 2018;Sadeghian et al 2019;Salzmann et al 2020;Xu, Hayet, and Karamouzas 2022). Graph-based models that utilize distance-based physical adjacency matrices (Mohamed et al 2020;Bae and Jeon 2021; or attention-based learnable adjacency matrices (Huang et al 2019;Shi et al 2021;Duan et al 2022;Wu et al 2023) to learn pedestrian social interactions have also been developed. Besides, transformer-based models incorporate attention mechanisms (Yu et al 2020;Yuan et al 2021;Tsao et al 2022) to model social interaction for better performance in pedestrian trajectory prediction tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Very recently, flow-based models (Liang et al 2023) and diffusion models (Mao et al 2023) were also applied in trajectory prediction tasks. Many methods proposed recently adopted goal-guided strategies and presented remarkable performance improvements Duan et al 2022;Xu et al 2022), but they ignored diverse motions in non-goal time steps, as shown in Fig. 2.…”
Section: Related Workmentioning
confidence: 99%